2017
DOI: 10.1186/s12889-017-4612-1
|View full text |Cite|
|
Sign up to set email alerts
|

The shrinking health advantage: unintentional injuries among children and youth from immigrant families

Abstract: BackgroundImmigrants typically arrive in good health. This health benefit can decline as immigrants adopt behaviours similar to native-born populations. Risk of injury is low in immigrants but it is not known whether this changes with increasing time since migration. We sought to examine the association between duration of residence in Canada and risk of unintentional injury.MethodsPopulation-based cross-sectional study of children and youth 0 to 24 years in Ontario, Canada (2011-2012), using linked health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…Our findings also provide further documentation of the heterogeneity of the immigrant population, as injury incidence differed considerably between regions and countries of origin. In accordance with other studies (Aamodt et al 2020 ; Saunders et al 2018 ), we found particularly low incidence rates for immigrants originating from Asia (especially Southeast Asia), whereas rates were highest for immigrants from Western countries, which are culturally more similar to Norway. Our study also corroborates earlier findings from Scandinavian and other Western countries showing lower risk of poisoning (Saunders et al 2017 ) and fractures (Aamodt et al 2020 ) in immigrant groups, but higher risk of burns (Laursen and Moller 2009 ; Karimi et al 2015 ; Elrod et al 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings also provide further documentation of the heterogeneity of the immigrant population, as injury incidence differed considerably between regions and countries of origin. In accordance with other studies (Aamodt et al 2020 ; Saunders et al 2018 ), we found particularly low incidence rates for immigrants originating from Asia (especially Southeast Asia), whereas rates were highest for immigrants from Western countries, which are culturally more similar to Norway. Our study also corroborates earlier findings from Scandinavian and other Western countries showing lower risk of poisoning (Saunders et al 2017 ) and fractures (Aamodt et al 2020 ) in immigrant groups, but higher risk of burns (Laursen and Moller 2009 ; Karimi et al 2015 ; Elrod et al 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, we do not expect that these sources of misclassification differ systematically according to immigrant status. Potential extensions to the work reported in the current study include explorations of how immigrants' use of primary and secondary care for treatment of injuries varies according to other factors known to affect health care utilisation, such as duration of stay in the host country and reason for migration (Saunders et al 2018;McDonald and Kennedy 2004;Diaz et al 2015a;Diaz and Kumar 2014;Norredam et al 2014;Diaz et al 2015b;Elstad 2016). Another avenue for future research involves assessing whether health care utilisation among immigrants differs by type of service (i.e., GPs vs. EPHC in primary care and inpatient vs. outpatient treatment in secondary care).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Sample sizes varied widely, depending on the study design, from one parent's observations of their son playing outdoors 27 to 999 951 data points on unintentional injuries among children and youth collected from linked health and administrative databases. 28 Outdoor play themes Figure 3 shows the distribution of included articles according to these priority themes and year of publication.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…pays dans le cadre d'une seule étude26 . La taille de l'échantillon variait considérablement en fonction du type d'étude, allant des observations d'un seul parent au sujet des jeux en plein air de son enfant27 à 999 951 points de données sur les blessures involontaires chez les enfants et les jeunes tirés de bases de données administratives et sur la santé pertinentes28 .…”
unclassified